Gold Nanostars: Synthesis, Optical and SERS Analytical Properties. Issue 3 (30th March 2022) - Becerril‐Castro, I. Brian; Calderon, Irene; Pazos‐Perez, Nicolas; Guerrini, Luca; Schulz, Florian; Feliu, Neus; Chakraborty, Indranath; Giannini, Vincenzo; Parak, Wolfgang J.; Alvarez‐Puebla, Ramon A.
Abstract: Gold nanostars are among the most efficient plasmonic nanomaterials for optical sensing with surface enhanced Raman scattering. In recent years, gold nanostars have increased relevance in physics, analytical chemistry, environmental science, biology and medicine, and in particular in sensing and therapy. These colloids can sustain ultrastrong electromagnetic fields which allow their use as single particles optical enhancers; are colloidally stable and may have a marked catalytical activity. Due to their exotic shape, these colloids present characteristic optical and reactive behaviors. Here, we briefly discuss the optical properties, the synthetic routes and the analytical applications of these nanoparticles. Abstract : Nanostar‐shaped gold nanoparticles are among the most efficient plasmonic materials for surface‐enhanced Raman scattering (SERS) applications, enabling single‐particle analysis. This Review summarizes and discusses the state‐of‐the‐art synthetic approaches as well as the strict correlation of the optical properties of this intriguing class of nanomaterials with their morphological features. Finally, representative examples of their implementation into analytical SERS applications are illustrated.